Tribal-State Relations - Loring, Donna (Maine Policy Review, 2004)
Donna Loring’s commentary provides an alternative perspective on Native American sovereignty in Maine, looking at the sometimes contentious process of tribal-state relations.
Keywords: Maine Indians; tribal-state relations